Self-reported hearing loss and instrumental activities of daily living among community-dwelling older adults in India: Results of a national survey in 2017-2018 - Peltzer K. (2023)
This study aimed to assess the association between hearing loss and seven Instrumental Activities of Daily Living (IADL) among older adults in India. The cross-sectional sample consisted of 31,477 individuals (≥60 years) from the Longitudinal Ageing Study in India (LASI) Wave 1 in 2017-2018. Results indicate that the prevalence of no hearing loss was 90.1%, hearing loss and no hearing aid 9.5%, and hearing loss plus hearing aid 0.4%. Among those with hearing loss only 4.3% reported using hearing aids. In the adjusted logistic regression analysis, compared to persons with no hearing loss, people with hearing loss and no hearing aid had a higher odds of IADL 1 (preparing hot meals) (Adjusted Odds Ratio-AOR: 1.47, Confidence Interval-CI: 1.11-193), IADL 3 (telephone calls) (AOR: 1.23, CI: 1.01-1.46), IADL 5 (house or garden work) (AOR: 1.56, CI: 1.19-2.03), IADL 6 (managing money) (AOR: 1.59, CI: 1.17-2.14), and IADL 7 (getting around) (AOR: 1.56, CI: 1.17-2.09). Compared to persons with no hearing loss, people with hearing loss and with hearing aid did not significantly differ on all of the seven IADLs. One in ten older adults in India reported hearing loss. We found a positive association between hearing loss without hearing aid and difficulty with five IADLs, and the associations were not significant in those with hearing loss and with hearing aid.